KONSEP HUBUNGAN KEWENANGAN ANTARA PEMERINTAH PUSAT DAN PEMERINTAH DAERAH DALAM BINGKAI NEGARA KESATUAN DENGAN CORAK OTONOMI LUAS - Robuwan, Rahmat; Wirazilmustaan, Wirazilmustaan; Agustian, Rio Armanda (PROGRESIF: Jurnal Hukum, 2018)
State of Indonesia is a very large country. It can be seen from many tribes, nations, cultures, languages, and others who are in Indonesia. As a unitary state with extensive autonomy, takes the concept of the relationship of authority between the central government and local governments. Administratively, the pattern of the relationship of authority between the central government and regional governments born of the delegation of authority. Who was born on the theory of delegation, supervision concept embraced by local governments in Indonesia are more inclined to form Hybrid variations (supervision), transfer of power from central to local government could be said to embrace open-end arrangement or general competence. therefore, a new paradigm in central and local relations should be established with the pattern of center-periphery relations towards a more harmonious, it's time developed progressive thinking that is based on relations that are complementary and interdependent.